Strategies to Overcome Marine Pollution Caused by Plastic Waste to Protect Marine Environment in Indonesia - R. Eriska Ginalita Dwi Putri; Idris Idris; R.A. Gusman Catur; Immamulhadi Immamulhadi (Universitas Muhammadiyah Purwokerto, 2021)
Nowadays marine pollution become a serious problem in the world espesially in Indonesia. Marine scientists have found harmful impact of marine pollution to marine environment, ecosystem and humans, there-quarter of all marine debris is plastic, a persistent and potentially hazardous pollutan. Plastic can be chemically harmful to wildlife, either because themselves potentially toxic or other toxic pollutan, the situation become worse when it come to marrine pollution caused by micro plastic, micro plastic is very dangerous for the ecosystem and the human in the world. Public awaarness to participate in maintaining the marine environment is decreasing day by day. Some people do not realise that microplastic are so danger to marine environment because most plastics in the ocean break up into very small particles, plastic is one of the kind of marine debris and it can come in all shapes and size, but those that are less than five millimeter in length. Indonesia is the second-biggest-contributor to ocean after China, with some estimates suggesting it is source of about 10% of global plastic pollution, if this problem can not be solved, there could be more plastic than fish in the ocean. Unfortunetly up to present we do not have any effective methode to clean up the ocean, the only thing that we can do is reduce the use of plastic in daily life. Marine pollution is become global problem so that is why we need some strategies to solved this problem, based on internatinal frame work Indonesia and others contries should do cooperation with others country and based on national legal frame works government should make special regulation to protect marine environment. Pollution from land-based sources, either direcly by urban or argiculuture discharger or indirecly through water. Keyword: Marrine, Pollution, ASEAN